2004
DOI: 10.1210/en.2003-1754
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY3–36Inhibits Food Intake in Mice through a Melanocortin-4 Receptor-Independent Mechanism

Abstract: Peptide YY(3-36) (PYY(3-36)), a peptide released postprandially by the gut, has been demonstrated to inhibit food intake. Little is known about the mechanism by which PYY(3-36) inhibits food intake, although the peptide has been shown to increase hypothalamic proopiomelanocortin (POMC) mRNA in vivo and to activate POMC neurons in an electrophysiological slice preparation. Understanding the physiology of PYY(3-36) is further complicated by the fact that some laboratories have had difficulty demonstrating inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(182 citation statements)
references
References 25 publications
12
164
2
4
Order By: Relevance
“…Both PYY1-36 [8,9] and PYY3-36 suppress appetite and food intake in rodents [10][11][12][13][14]. However, one report was unable to confirm this finding [15].…”
Section: Introductionmentioning
confidence: 99%
“…Both PYY1-36 [8,9] and PYY3-36 suppress appetite and food intake in rodents [10][11][12][13][14]. However, one report was unable to confirm this finding [15].…”
Section: Introductionmentioning
confidence: 99%
“…The gut hormones peptide YY (PYY) and glucagon-like peptide (GLP)-1 are co-secreted from intestinal enteroendocrine L-cells and released post-prandially in proportion to the amount of energy ingested (Ghatei et al, 1983;Adrian et al, 1985;Le Roux et al, 2006). PYY and GLP-1 have both been shown to be satiety factors, reducing food intake when administered to rodents (Batterham et al, 2002;Challis et al, 2003;Halatchev et al, 2004;Chelikani et al, 2005aChelikani et al, , b, 2006Talsania et al, 2005) and to humans (Flint et al, 1998;Gutzwiller et al, 1999;Batterham et al, 2002;Degen et al, 2005;Le Roux et al, 2006). The incretin effect of GLP-1, augmentation of insulin secretion in response to an oral glucose load, has been well characterised (Elrick et al, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated acute affects of PYY1-36 and PYY3-36 in inhibiting food intake in animals and in man (Adams et al, 2004, Batterham et al, 2002, Challis et al, 2003, Chelikani et al, 2004, Chelikani et al, 2005, Halatchev et al, 2004and Riediger et al, 2004. It is thought that after a meal, PYY3-36, the main form of PYY circulating postprandially, acts on the arcuate nucleus of the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%